Anesthetic Management of Patients with Congenital Insensitivity to Pain with Anhidrosis: A Retrospective Analysis of 358 Procedures Performed Under General Anesthesia. (November 2015) - Zlotnik, Alexander; Natanel, Dmitry; Kutz, Ruslan; Boyko, Matthew; Brotfain, Evgeny; Gruenbaum, Benjamin F.; Gruenbaum, Shaun E.; Bodner, Lipa
Abstract : BACKGROUND: Congenital insensitivity to pain with anhidrosis (CIPA) is a rare autosomal recessive disorder characterized by recurrent episodic fevers, anhidrosis, absent reaction to noxious stimuli, self-mutilating behavior, and mental retardation. The anesthetic management of patients with CIPA is challenging. Autonomic nervous system abnormalities are common, and patients are at increased risk for perioperative complications. METHODS: In this study, we describe our experience with 35 patients with CIPA who underwent 358 procedures requiring general anesthesia between 1990 and 2013. RESULTS: During surgery, 3 patients developed hyperthermia intraoperatively (>37.5°C) without prior fever. There were no cases of intraoperative hyperpyrexia (>40°C). Aspiration was suspected in 2 patients, and in another patient aspiration was prevented by the use of endotracheal tube, early detection of regurgitation, and aggressive suctioning. One patient had cardiac arrest requiring cardiopulmonary resuscitation. Intraoperative bradycardia was observed in 10 cases, and postoperative bradycardia was observed in 11 cases. CONCLUSIONS: Regurgitation, hyperthermia, and aspiration were uncommon, but the incidence of bradycardia was higher than has been reported in previous studies. CIPA remains a challenge for anesthesiologists. Because of the rare nature of this disorder, the risk of various complications is difficult to predict.